A method for preparing starch-polyphenol nanostructure network

The starch chain breakage and crosslinking was induced by microjet and ball milling treatment, combined with high-temperature reaction and non-polar polyphenols, and a high-load starch-polyphenol nanostructure network was successfully prepared, solving the complexity and non-polarity of starch multi-level structures The problem of difficulty in applying polyphenols has achieved efficient and green nanostructure network preparation.

CN118994423BActive Publication Date: 2025-02-18ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411479866.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

It is difficult to regulate the starch macromolecule to nanostructure network, especially non-polar polyphenols are difficult to apply due to poor water solubility, strong crystallinity, and large size.

Method used

The high-pressure impact of the microjet is used to induce the starch chain to break and produce free radicals. The gelatinized starch chain expands to form flexible chains, and the starch nanostructure network is induced to generate free radicals through ball milling, and it is used to treat non-polar polyphenols under high temperature conditions. Highly efficient reactions form high-loaded starch-polyphenol nanostructure networks.

Benefits of technology

The preparation of a high-load starch-polyphenol nanostructure network is achieved, combined with the advantages of high phenol content, uniform distribution and high yield, and has antibacterial effects. It is a good material for enhancing membrane performance and delivering drugs, expanding its use in medicine, Applications in cosmetics, food and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994423B_ABST
    Figure CN118994423B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a starch-polyphenol nanostructure network, the method comprising the following steps: (1) preparing a starch suspension; (2) thermal gelatinization; (3) microfluidization treatment; (4) heat treatment; (5) vacuum freeze drying; (6) ball milling treatment; (7) high temperature reaction; (8) alcohol precipitation treatment; (9) centrifugation treatment; (10) vacuum freeze drying. The present invention utilizes physical field microfluidization to induce the formation of starch short chains with free radicals, drives the short chains to crosslink and entangle into a starch nanonetwork through heat treatment, and induces the generation of free radicals on the surface of the network structure again through ball milling, thereby promoting the covalent bonding of starch chains and polyphenols, and preparing a starch-polyphenol nanostructure network with a high loading rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a starch-polyphenol nanostructure network, in particular to a preparation method of a starch-polyphenol nanostructure network. Background Art

[0002] Polyphenols are widely used in food, medicine, chemical industry, agriculture and other fields due to their excellent antioxidant, anti-inflammatory, anti-thrombotic and antibacterial physiological functions. Polyphenols include polar polyphenols and non-polar polyphenols. Non-polar polyphenols such as ferulic acid, curcumin, epigallocatechin gallate, etc. are difficult to apply due to their poor water solubility, strong crystallinity and large size. Micro-nanostructured networks have great potential in structural applications due to their excellent mechanical properties and thermal stability at the nanoscale. Starch, as a natural macromolecule, has a wide range of sources and strong modifiability, so it is considered to be an ideal nanonetwork carrier. Based on this, constructing a starch-polyphenol nanostructured network helps to broaden the application of polyphenol active ingredients.

[0003] However, the multi-level structure of starch is complex (from basic glucose units, short starch chains, long straight chains / branches of starch and the diverse spatial structures formed by them), and it is difficult to regulate starch macromolecules into nanostructured networks. Summary of the invention

[0004] The invention provides a method for preparing a starch-polyphenol nanostructure network. The method utilizes the high-pressure impact of a microjet to induce starch chain scission to generate free radicals. The gelatinized starch chains expand and are converted from rigid chains to flexible chains. In a microjet cavity, starch solution droplets collide with each other and rub against the cavity surface under high-pressure and high-speed impact, resulting in starch chain scission accompanied by the generation of free radicals, thereby cross-linking to form a starch nanostructure network. The starch nanostructure network is induced to generate free radicals again through ball milling, and the starch nanostructure network is efficiently reacted with non-polar polyphenols under high temperature conditions to form a high-load starch-polyphenol nanostructure network.

[0005] In order to achieve the above-mentioned object, the technical solution of the present application is as follows: A method for preparing a high-load starch-polyphenol nanostructure network comprises the following steps:

[0006] (1) Preparing starch suspension: dispersing starch in water to obtain starch suspension;

[0007] (2) Thermal gelatinization: The starch suspension is gelatinized in a boiling water bath and then cooled to room temperature to obtain starch solution A. After gelatinization, the starch chains expand and transform from rigid chains to flexible chains.

[0008] (3) Microfluidization: Starch solution A is treated with microfluidization to obtain starch solution B. In the microfluidizer cavity, starch solution droplets collide with each other and rub against the cavity surface under high pressure and high speed impact, resulting in starch chain scission and the generation of free radicals.

[0009] (4) Heat treatment: The starch solution B is heat treated by incubating the starch solution B in a 50°C water bath for 30 min. The heat treatment after microfluidization can drive the short chains with free radicals to crosslink and entangle to form a nanostructure network.

[0010] (5) Vacuum freeze drying: freeze drying the heat-treated starch solution B to obtain a freeze-dried powder having a starch nanonetwork;

[0011] (6) Ball milling: The freeze-dried powder is subjected to ball milling to obtain ball milled powder. The frequency and time of ball milling determine the input energy. When the frequency and time reach a certain level, they can induce the generation of surface free radicals in the nanonetwork, thereby facilitating the reaction loading with polyphenols.

[0012] (7) High temperature reaction: polyphenols are added to the ball-milled powder for high temperature reaction to obtain a sample solution; the high temperature reaction is to place polyphenols and starch solution C with a mass ratio of 3:1 to 1:1 in a 95°C water bath and magnetically stir at 500 rpm for 1 h; during the high temperature esterification reaction, the mass ratio of phenolic acid to starch also affects the yield of starch-polyphenol nanonetworks;

[0013] (8) Alcohol precipitation: The sample solution is subjected to alcohol precipitation to dissolve free polyphenols;

[0014] (9) Centrifugation: The sample solution after alcohol precipitation is centrifuged to remove the supernatant and obtain the precipitate;

[0015] (10) Vacuum freeze drying: Freeze-dry the precipitate to obtain sample powder.

[0016] Furthermore, the starch is one or more of corn starch, potato starch, mung bean starch, highland barley starch, rice starch, wheat starch, and cassava starch; in the starch suspension, the mass ratio of starch to water is 3-5:100.

[0017] Furthermore, the boiling water bath gelatinization process is as follows: in a 100° C. water bath, magnetic stirring is performed at a speed of 500 rpm for 30 minutes.

[0018] Furthermore, the microjet treatment conditions are: using a "Y"-type or "Z"-type microjet reactor, the channel of the microjet reactor is single-channel or multi-channel, the channel size is 75-200μm; the pressure is ≥50MPa, the repeated injection is ≥1 times, and the injection rate is 20-150mL / min.

[0019] Furthermore, the ball milling treatment conditions in step (6) are: frequency ≥ 60 Hz, time ≥ 10 min.

[0020] Furthermore, the polyphenols are one or more of ferulic acid, curcumin, and epigallocatechin gallate.

[0021] Furthermore, the alcohol precipitation conditions of the alcohol precipitation treatment are: anhydrous ethanol is uniformly dripped into the sample solution at a speed of 150 mL / min, stirring is maintained during the alcohol precipitation process, the stirring speed is 1000 r / min, and the volume ratio of anhydrous ethanol to the sample solution is 1.5:1.

[0022] Furthermore, the centrifugation condition is: centrifugation at 8000 rpm for 5 min.

[0023] Furthermore, the freeze-drying conditions in step (5) and step (10) are: vacuum drying at -60°C for 48 hours.

[0024] The beneficial effects of the present invention are as follows: the present invention uses physical field microfluidization to induce the formation of starch short chains with free radicals, drives the short chains to crosslink and entangle into starch nano networks through heat treatment, and induces the generation of free radicals on the surface of the network structure again through ball milling, thereby promoting the covalent binding of starch chains and polyphenols, and preparing a starch-polyphenol nanostructure network with a high loading rate. The present invention proposes an efficient and green physical field processing technology for preparing a starch-polyphenol nanostructure network. The starch-polyphenol nanostructure network has the advantages of high content of bound phenol, uniform distribution, high yield, etc., has antibacterial effect, is a good material for enhancing membrane performance and delivering drugs, and expands its application in the fields of medicine, cosmetics, food, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flow chart for preparing a high-load polyphenol-starch ester;

[0026] Figure 2 (a) is a scanning electron microscope image (SEM) of Example 1, Figure 2 (b) is the SEM image of Example 2. Figure 2 (c) is the SEM image of Example 3. Figure 2 (d) is the SEM image of Example 4. Figure 2 (e) is the SEM image of Comparative Example 1. Figure 2 (f) is the SEM image of Comparative Example 2. Figure 2 (g) is the SEM image of Comparative Example 3. Figure 2 (h) is the SEM image of Comparative Example 4. Figure 2 (i) is the SEM image of Comparative Example 5, Figure 2 (j) is the SEM image of Comparative Example 6. Figure 2 (k) is the SEM image of Comparative Example 7;

[0027] Figure 3(a) is the combined phenol content diagram of Example 1, Figure 3 (b) is the combined phenol content diagram of Example 2, Figure 3 (c) is the combined phenol content diagram of Example 3, Figure 3 (d) is the combined phenol content diagram of Example 4, Figure 3 (e) is the combined phenol content diagram of Comparative Example 1, Figure 3 (f) is the combined phenol content diagram of Comparative Example 2, Figure 3 (g) is the combined phenol content diagram of Comparative Example 3, Figure 3 (h) is the combined phenol content diagram of Comparative Example 4;

[0028] Figure 4 (a) is the Fourier transform infrared spectrum (FTIR) of Example 1, Figure 4 (b) is the FTIR graph of Example 4. Figure 4 (c) is the FTIR graph of Comparative Example 1. Figure 4 (d) is the FTIR graph of Comparative Example 2. Figure 4 (e) is the FTIR graph of Comparative Example 3. Figure 4 (f) is the FTIR graph of Comparative Example 4;

[0029] Figure 5 (a) is the X-ray photoelectron spectroscopy (XPS) of Example 1, Figure 5 (b) is the X-ray photoelectron spectrum (XPS) of Example 4;

[0030] Figure 6 (a) is the carbon nuclear magnetic resonance spectrum (13C-NMR) of Example 1, Figure 6 (b) is the 13C-NMR chart of Example 4. DETAILED DESCRIPTION

[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0032] The present invention utilizes physical field micro-jet to induce the formation of starch short chains with free radicals. The starch chains expand after gelatinization and are converted from rigid chains to flexible chains. In the micro-jet cavity, starch solution droplets collide with each other and rub against the cavity surface under high pressure and high speed impact, resulting in starch chain scission, accompanied by the generation of free radicals. The heat treatment after micro-jet can drive the short chains with free radicals to cross-link and entangle to form a nanostructure network. After the nanostructure network is formed, the frequency and time of ball milling determine the input energy. Only when the frequency and time reach a certain level can the generation of surface free radicals of the nano-network be induced, thereby facilitating the reaction load with polyphenols. During the high-temperature esterification reaction, phenolic acid and starch form a starch-polyphenol nano-network.

[0033] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0034] Example 1

[0035] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0036] (1) preparing a starch suspension: dispersing 3% by weight corn starch in water to obtain a starch suspension;

[0037] (2) Thermal gelatinization: The starch suspension was placed in a 100°C water bath with magnetic stirring at 500 rpm for 30 min for gelatinization, and then cooled to room temperature to obtain starch solution A.

[0038] (3) Microfluidization treatment: Starch solution A was injected into a microfluidizer. The microfluidizer structure was a "Y"-shaped single channel with a channel size of 75 μm. The microfluidizer pressure was set to 50 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min to obtain starch solution B.

[0039] (4) Heat treatment: Incubate the obtained starch solution B in a 50°C water bath for 30 min;

[0040] (5) Vacuum freeze-drying: The heat-treated starch solution B is vacuum dried at -60°C for 48 h to obtain a freeze-dried powder having a starch nanonetwork;

[0041] (6) Ball milling: The freeze-dried powder was placed in a ball mill at a frequency of 60 Hz for 10 min to obtain ball-milled powder ink;

[0042] (7) High temperature reaction: ferulic acid and ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h to obtain a sample solution;

[0043] (8) Alcohol precipitation: Anhydrous ethanol was dripped into the sample solution at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min, and the volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0044] (9) Centrifugation: The sample solution after alcohol precipitation is centrifuged to remove the supernatant. The centrifugation conditions are: centrifugation at 8000 rpm for 5 min to obtain the precipitate.

[0045] (10) Vacuum freeze-drying: The precipitate was vacuum-dried at -60 °C for 48 h to obtain sample powder.

[0046] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0047] Morphological observation: Figure 2 In (a), the starch-polyphenol nanostructure network was coated on the conductive glue and gold was sprayed for scanning electron microscopy (SEM) observation.

[0048] Phenol binding content: Figure 3 In (a), the starch-polyphenol nanostructure network was degraded and extracted, and then detected by high performance liquid chromatography (HPLC) to calculate the bound phenol content.

[0049] Structural observation: Figure 4 (a) Figure 5 (a) Figure 6 In (a), the starch-polyphenol nanostructure network was measured by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and carbon nuclear magnetic resonance (13C-NMR).

[0050] From SEM, FTIR, XPS and 13C-NMR, the starch-polyphenol nanostructure network was successfully prepared in this example, and its bound phenol content was 5.33%.

[0051] Example 2

[0052] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0053] (1) Preparation of starch suspension: Disperse 5% wt starch in water to obtain a starch suspension, wherein the ratio of rice starch to potato starch is 1:1 / w:w;

[0054] (2) Thermal gelatinization: The starch suspension was placed in a 100°C water bath with magnetic stirring at 500 rpm for 30 min for gelatinization, and then cooled to room temperature to obtain starch solution A.

[0055] (3) Microfluidization treatment: Starch solution A was injected into a microfluidizer. The microfluidizer structure was a "Y"-shaped multi-channel reactor with a channel size of 200 μm. The microfluidizer pressure was set to 200 MPa, the number of repeated injections was 30 times, and the injection rate was 70 mL / min to obtain starch solution B.

[0056] (4) Heat treatment: Incubate the obtained starch solution B in a 50°C water bath for 30 min;

[0057] (5) Vacuum freeze-drying: The heat-treated starch solution B is vacuum dried at -60°C for 48 h to obtain a freeze-dried powder having a starch nanonetwork;

[0058] (6) Ball milling: The freeze-dried powder was placed in a ball mill at a frequency of 200 Hz for 60 min to obtain ball milled powder;

[0059] (7) High temperature reaction: Curcumin and the above powder were mixed into a solution (curcumin: starch = 2:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h to obtain a sample solution;

[0060] (8) Alcohol precipitation: Anhydrous ethanol was dripped into the sample solution at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min, and the volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0061] (9) Centrifugation: The sample solution after alcohol precipitation is centrifuged to remove the supernatant. The centrifugation conditions are: centrifugation at 8000 rpm for 5 min to obtain the precipitate;

[0062] (10) Vacuum freeze-drying: The precipitate was vacuum-dried at -60 °C for 48 h to obtain sample powder.

[0063] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0064] Morphological observation: Figure 2 In (b), the sample powder is coated on the conductive glue and gold is sprayed, and a scanning electron microscope (SEM) is used for observation. In this embodiment, a starch-polyphenol nanostructure network is successfully prepared.

[0065] Phenol binding content: Figure 3 In (b), the sample powder was degraded and extracted, and then tested by high performance liquid chromatography (HPLC) to calculate the bound phenol content, which was 17.34%.

[0066] Example 3

[0067] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0068] (1) Preparation of starch suspension: 3% wt starch was dispersed in water to obtain a starch suspension, wherein the ratio of mung bean starch: highland barley starch: wheat starch: tapioca starch was 1:1:1:1 / w:w:w:w;

[0069] (2) Thermal gelatinization: The starch suspension was placed in a 100°C water bath with magnetic stirring at 500 rpm for 30 min for gelatinization, and then cooled to room temperature to obtain starch solution A.

[0070] (3) Microfluidization treatment: Starch solution A was injected into a microfluidizer. The microfluidizer structure was a "Z"-shaped single channel with a channel size of 110 μm. The microfluidizer pressure was set to 100 MPa, the number of repeated injections was 10 times, and the injection rate was 150 mL / min to obtain starch solution B.

[0071] (4) Heat treatment: Incubate the obtained starch solution B in a 50°C water bath for 30 min;

[0072] (5) Vacuum freeze-drying: The heat-treated starch solution B is vacuum dried at -60°C for 48 h to obtain a freeze-dried powder having a starch nanonetwork;

[0073] (6) Ball milling: The freeze-dried powder was placed in a ball mill at a frequency of 100 Hz for 25 min to obtain ball milled powder;

[0074] (7) High temperature reaction: Epigallocatechin gallate and ball-milled powder were mixed into a solution (epigallocatechin gallate: starch = 3:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h to obtain a sample solution;

[0075] (8) Alcohol precipitation: Anhydrous ethanol was dripped into the sample solution at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min, and the volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0076] (9) Centrifugation: The sample solution after alcohol precipitation is centrifuged to remove the supernatant. The centrifugation conditions are: centrifugation at 8000 rpm for 5 min to obtain the precipitate;

[0077] (10) Vacuum freeze-drying: The precipitate was vacuum-dried at -60 °C for 48 h to obtain sample powder.

[0078] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0079] Morphological observation: Figure 2In (c), the sample powder is coated on the conductive glue and gold is sprayed, and a scanning electron microscope (SEM) is used for observation. In this embodiment, a starch-polyphenol nanostructure network is successfully prepared.

[0080] Phenol binding content: Figure 3 In (c), the sample powder was degraded and extracted, and then tested by high performance liquid chromatography (HPLC) to calculate the bound phenol content, which was 21.37%.

[0081] Example 4

[0082] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0083] (1) Preparing a starch suspension: dispersing 3% wt corn starch in water to obtain a starch suspension;

[0084] (2) Thermal gelatinization: The starch suspension was placed in a 100°C water bath with magnetic stirring at 500 rpm for 30 min for gelatinization, and then cooled to room temperature to obtain starch solution A.

[0085] (3) Microfluidization treatment: Starch solution A was injected into a microfluidizer. The microfluidizer structure was a "Z"-shaped multi-channel reactor with a channel size of 150 μm. The microfluidizer pressure was set to 150 MPa, the number of repeated injections was 20 times, and the injection rate was 120 mL / min to obtain starch solution B.

[0086] (4) Heat treatment: Incubate the obtained starch solution B in a 50°C water bath for 30 min;

[0087] (5) Vacuum freeze-drying: The heat-treated starch solution B is vacuum dried at -60°C for 48 h to obtain a freeze-dried powder having a starch nanonetwork;

[0088] (6) Ball milling: The freeze-dried powder was placed in a ball mill at a frequency of 150 Hz for 40 min to obtain ball milled powder;

[0089] (7) High temperature reaction: ferulic acid and ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h to obtain a sample solution;

[0090] (8) Alcohol precipitation: Anhydrous ethanol was dripped into the sample solution at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min, and the volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0091] (9) Centrifugation: The sample solution after alcohol precipitation is centrifuged to remove the supernatant. The centrifugation conditions are: centrifugation at 8000 rpm for 5 min to obtain the precipitate;

[0092] (10) Vacuum freeze-drying: The precipitate was vacuum-dried at -60 °C for 48 h to obtain sample powder.

[0093] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0094] Morphological observation: Figure 2 In (d), the sample powder is coated on the conductive glue and gold is sprayed, and then observed by scanning electron microscopy (SEM).

[0095] Phenol binding content: Figure 3 In (d), the sample powder was degraded and extracted, and then detected by high performance liquid chromatography (HPLC) to calculate the bound phenol content.

[0096] Structural observation: Figure 4 (b) Figure 5 (b) Figure 6 In (b), the sample powder was measured by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and carbon nuclear magnetic resonance (13C-NMR).

[0097] From SEM, FTIR, XPS and 13C-NMR, the starch-polyphenol nanostructure network was successfully prepared in this example, and its bound phenol content was 18.33%.

[0098] Comparative Example 1

[0099] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0100] Preparation of gelatinized starch suspension: Disperse 2% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0101] Microfluidization treatment: The starch solution was injected into a microfluidizer. The microfluidizer had a Y-shaped single channel structure with a channel size of 75 μm. The microfluidizer pressure was set to 50 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min.

[0102] Heat treatment: The microfluidization-treated solution was incubated in a 50°C water bath for 30 min.

[0103] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0104] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 60 Hz for 10 min to obtain ball milled powder.

[0105] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0106] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0107] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0108] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0109] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0110] Morphological observation: Figure 2 In (e), the sample powder obtained in step (9) is coated on the conductive glue and gold is sprayed, and a scanning electron microscope (SEM) is used for observation.

[0111] Phenol binding content: Figure 3 In (e), the sample obtained in step (9) is degraded and extracted, and then detected by high performance liquid chromatography (HPLC) to calculate the content of bound phenol.

[0112] Structural observation: Figure 4 In (c), the Fourier transform infrared spectrum (FTIR) of the sample obtained in step (9) is measured.

[0113] From FTIR and SEM, the starch-polyphenol nanostructure network was not obtained in this example, and its bound phenol content was 0.50%. Compared with Example 1, it can be seen that the lower starch concentration is not conducive to the induction of starch chain free radicals and the generation of short chains by microjetting, and it is difficult to form a nano-network structure, resulting in insufficient free radicals generated by ball milling, so that the bound phenol content is also low.

[0114] Comparative Example 2

[0115] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0116] Preparation of gelatinized starch suspension: Disperse 3% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0117] Microfluidization treatment: The starch solution was injected into a microfluidizer. The microfluidizer had a Y-shaped single channel structure with a channel size of 75 μm. The microfluidizer pressure was set to 20 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min.

[0118] Heat treatment: The microfluidization-treated solution was incubated in a 50°C water bath for 30 min.

[0119] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0120] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 60 Hz for 10 min to obtain ball milled powder.

[0121] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0122] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0123] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0124] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0125] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0126] Morphological observation: Figure 2 In (f), the sample powder obtained in step (9) is coated on the conductive glue and gold is sprayed on it for scanning electron microscopy (SEM) observation.

[0127] Phenol binding content: Figure 3 In (f), the sample obtained in step (9) is degraded and extracted, and then detected by high performance liquid chromatography (HPLC) to calculate the bound phenol content.

[0128] Structural observation: Figure 4 In (d), the sample obtained in step (9) is measured for Fourier transform infrared (FTIR) spectrum.

[0129] From FTIR and SEM, the starch-phenol nanonetwork was not obtained in this example, and the bound phenol content was 0.33%. Compared with Example 1, it can be seen that the lower microjet pressure leads to weak microjet mechanical force, making it difficult to induce starch chains to produce free radicals and short chains, and difficult to form a nanonetwork structure, and leads to insufficient free radicals produced by ball milling, so that the bound phenol content is also low, and polyphenols and starch are mainly bound by hydrogen bonds, and the binding force is weak.

[0130] Comparative Example 3

[0131] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0132] Preparation of gelatinized starch suspension: Disperse 3% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0133] Heat treatment: The microfluidization-treated solution was incubated in a 50°C water bath for 30 min.

[0134] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0135] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 60 Hz for 10 min to obtain ball milled powder.

[0136] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0137] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0138] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0139] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0140] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0141] Morphological observation: Figure 2 In (g), the sample powder obtained in step (8) is coated on the conductive glue and gold is sprayed, and a scanning electron microscope (SEM) is performed for observation.

[0142] Phenol binding content: Figure 3 In (g), the sample obtained in step (8) is degraded and extracted, and then detected by high performance liquid chromatography (HPLC) to calculate the bound phenol content.

[0143] Structural observation: Figure 4 In (e), the sample obtained in step (8) is measured for Fourier transform infrared spectrum (FTIR).

[0144] From FTIR and SEM, the starch-polyphenol nanostructure network was not obtained in this example, and its bound phenol content was 0.44%. Compared with Example 1, it can be seen that the importance of microfluidization treatment for the formation of polyphenol-starch esters can be seen. Microfluidization can induce starch chains to produce short chains with free radicals, thereby promoting the ball milling process.

[0145] Comparative Example 4

[0146] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0147] Preparation of gelatinized starch suspension: Disperse 3% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0148] Microfluidization treatment: The starch solution was injected into a microfluidizer. The microfluidizer had a Y-shaped single channel structure with a channel size of 75 μm. The microfluidizer pressure was set to 50 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min.

[0149] Heat treatment: The microfluidization-treated solution was incubated in a 50°C water bath for 30 min.

[0150] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0151] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 60 Hz for 10 min to obtain ball milled powder.

[0152] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 0.1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0153] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0154] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0155] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0156] The morphological structure and phenol binding content of the prepared samples were characterized as follows:

[0157] Morphological observation: Figure 2 In (h), the sample powder obtained in step (9) is coated on the conductive glue and gold is sprayed, and a scanning electron microscope (SEM) is performed for observation.

[0158] Phenol binding content: Figure 3 In (h), the sample obtained in step (9) is degraded and extracted, and then detected by high performance liquid chromatography (HPLC) to calculate the bound phenol content.

[0159] Structural observation: Figure 4 In (f), the Fourier transform infrared spectrum (FTIR) of the sample obtained in step (9) is measured.

[0160] From FTIR and SEM, the starch-polyphenol nanostructure network was not obtained in this example, and its bound phenol content was 0.96%. Compared with Example 1, it can be seen that a lower mass ratio of polyphenol to starch is not conducive to the formation of starch-polyphenol nanostructure network.

[0161] Comparative Example 5

[0162] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0163] Preparation of gelatinized starch suspension: Disperse 3% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0164] Microfluidization treatment: The starch solution was injected into a microfluidizer. The microfluidizer had a Y-shaped single channel structure with a channel size of 75 μm. The microfluidizer pressure was set to 50 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min.

[0165] Heat treatment: The microfluidization-treated solution was incubated in a 50°C water bath for 30 min.

[0166] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0167] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 40 Hz for 10 min to obtain ball milled powder.

[0168] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0169] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0170] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0171] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0172] The morphology and structure of the prepared samples are as follows:

[0173] Morphological observation: Figure 2 In (i), the sample powder obtained in step (9) is coated on the conductive glue and sprayed with gold, and then observed by scanning electron microscopy (SEM).

[0174] From the SEM, no starch-polyphenol nanostructure network was obtained in this example. Compared with Example 1, it can be seen that when the ball milling frequency reaches a certain level, high enough energy can induce the formation of free radicals on the surface of the starch nanonetwork, promoting the loading of polyphenols to form a starch-polyphenol nanostructure network.

[0175] Comparative Example 6

[0176] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0177] Preparation of gelatinized starch suspension: Disperse 3% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0178] Microfluidization treatment: The starch solution was injected into a microfluidizer. The microfluidizer had a Y-shaped single channel structure with a channel size of 75 μm. The microfluidizer pressure was set to 50 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min.

[0179] Heat treatment: The microfluidization-treated solution was incubated in a 50°C water bath for 30 min.

[0180] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0181] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 60 Hz for 5 min to obtain ball milled powder.

[0182] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0183] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0184] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0185] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0186] The morphology and structure of the prepared samples are as follows:

[0187] Morphological observation: Figure 2 In (j), the sample powder obtained in step (9) is coated on the conductive glue and sprayed with gold, and then observed by scanning electron microscopy (SEM).

[0188] From the SEM, no starch-polyphenol nanostructure network was obtained in this example. Compared with Example 1, it can be seen that when the ball milling time reaches a certain level, high enough energy can induce the formation of free radicals on the surface of the starch nanonetwork, promoting the loading of polyphenols to form a starch-polyphenol nanostructure network.

[0189] Comparative Example 7

[0190] A method for preparing a highly loaded starch-polyphenol nanostructure network, such as Figure 1 As shown, the steps are as follows:

[0191] Preparation of gelatinized starch suspension: Disperse 3% wt corn starch in water to obtain a starch suspension, place it in a 100°C water bath, and magnetically stir it at 500 rpm for 30 min for gelatinization, and then cool it to room temperature.

[0192] Microfluidization treatment: The starch solution was injected into a microfluidizer. The microfluidizer had a Y-shaped single channel structure with a channel size of 75 μm. The microfluidizer pressure was set to 50 MPa, the number of repeated injections was 1, and the injection rate was 20 mL / min.

[0193] Freeze-drying treatment: The above-obtained solution was dried in a vacuum oven at -60°C for 48 h.

[0194] Ball milling: The above powders were placed in a ball mill for treatment at a frequency of 60 Hz for 10 min to obtain ball milled powder.

[0195] High temperature reaction: ferulic acid and the above-mentioned ball-milled powder were mixed into a solution (ferulic acid: starch = 1:1 / w:w) and placed in a 95°C water bath with magnetic stirring at 500 rpm for 1 h.

[0196] Alcohol precipitation treatment: anhydrous ethanol was dripped at a rate of 150 mL / min. Stirring was maintained during the alcohol precipitation process. The stirring speed was 1000 r / min. The volume ratio of anhydrous ethanol to sample solution was 1.5:1.

[0197] Centrifugation: Remove the supernatant by centrifugation at 8000 rpm for 5 min and retain the precipitate.

[0198] Freeze-drying treatment: The precipitate obtained above was dried in a vacuum oven at -60°C for 48 h.

[0199] The morphology and structure of the prepared samples are as follows:

[0200] Morphological observation: Figure 2 In (k), the sample powder obtained in step (8) is coated on the conductive glue and gold is sprayed, and a scanning electron microscope (SEM) is used for observation.

[0201] From the SEM, no starch-polyphenol nanostructure network was obtained in this example. Compared with Example 1, it can be seen that heat treatment is important for the formation of starch nanonetwork. After microfluidization treatment, starch forms short chains with free radicals, and heat treatment drives the short chains to crosslink and entangle to form a network.

[0202] It can be seen from the above embodiments and comparative examples that microfluidization treatment is particularly critical to the formation of starch-polyphenol nanonetworks. The starch chain after gelatinization expands and changes from a rigid chain to a flexible chain. In the microjet cavity, the starch solution droplets collide with each other under high-pressure and high-speed impact and rub against the cavity surface, resulting in starch chain scission, accompanied by the generation of free radicals. When the initial mass concentration of the starch solution and the microjet setting pressure reach a certain level, the function of the microjet in promoting the generation of starch free radicals is significant. When the initial mass concentration of the starch solution is low, the solution viscosity and density are low, which will cause the actual pressure of the sample after entering the cavity to become lower, affecting the force of the microjet on the starch chain. When the microjet setting pressure is low, the insufficient mechanical force causes the collision between the starch solution and the starch solution and the microjet cavity wall to weaken, affecting the chain scission effect of the starch chain and the generation of free radicals.

[0203] The heat treatment after microfluidization can drive the cross-linking and entanglement of short chains with free radicals to form a nanostructured network. After the nanostructured network is formed, the frequency and time of ball milling determine the input energy. When the frequency and time reach a certain level, the surface free radicals of the nanonetwork can be induced to generate, which is beneficial to the reaction loading with polyphenols. During the high-temperature esterification reaction, the mass ratio of phenolic acid to starch also affects the yield of starch-polyphenol nanonetwork. The esterification reaction is a reversible reaction. When the amount of phenolic acid added is insufficient, the esterification reaction cannot proceed forward, and the starch-polyphenol nanonetwork efficiency is low, which is manifested as insufficient final ester yield and low phenol binding content in the sample.

[0204] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a starch-polyphenol nanostructure network, characterized in that: The steps include: (1) Preparation of starch suspension: Disperse starch in water to obtain starch suspension; the mass ratio of starch to water is 3-5:100; (2) Thermal gelatinization: The starch suspension is gelatinized in a boiling water bath and then cooled to room temperature to obtain starch solution A. (3) Microfluidization treatment: Starch solution A is subjected to microfluidization treatment to obtain starch solution B; the microfluidization treatment conditions are: a "Y"-type or "Z"-type microfluidizer is used, the channel of the microfluidizer is a single channel or a multi-channel, and the channel size is 75-200 μm; the pressure is 50-200 MPa, the injection is repeated 1-30 times, and the injection rate is 20-150 mL / min; (4) Heat treatment: The starch solution B is heat treated by incubating the starch solution B in a 50°C water bath for 30 min; (5) Vacuum freeze drying: freeze drying the heat-treated starch solution B to obtain a freeze-dried powder having a starch nanonetwork; (6) Ball milling: ball milling the freeze-dried powder to obtain ball milled powder; the ball milling conditions are: frequency 60-200 Hz, time 10-60 min; (7) High temperature reaction: adding polyphenols to the ball-milled powder to perform a high temperature reaction to obtain a sample solution; the high temperature reaction is to place polyphenols and starch solution C in a mass ratio of 3:1 to 1:1 in a 95°C water bath and magnetically stir at 500 rpm for 1 h; (8) Alcohol precipitation: The sample solution is subjected to alcohol precipitation to dissolve free polyphenols; (9) Centrifugation: The sample solution after alcohol precipitation is centrifuged to remove the supernatant and obtain the precipitate; (10) Vacuum freeze drying: Freeze-dry the precipitate to obtain sample powder.

2. The preparation method according to claim 1, characterized in that: The starch is one or more of corn starch, potato starch, mung bean starch, highland barley starch, rice starch, wheat starch and cassava starch.

3. The preparation method according to claim 1, characterized in that: The boiling water bath gelatinization process is as follows: in a 100° C. water bath, magnetic stirring is performed at a speed of 500 rpm for 30 minutes.

4. The preparation method according to claim 1, characterized in that: The polyphenols are one or more of ferulic acid, curcumin, epigallocatechin gallate.

5. The preparation method according to claim 1, characterized in that: The alcohol precipitation conditions of the alcohol precipitation treatment are as follows: anhydrous ethanol is uniformly dripped into the sample solution at a speed of 150 mL / min, stirring is maintained during the alcohol precipitation process, the stirring speed is 1000 r / min, and the volume ratio of anhydrous ethanol to the sample solution is 1.5:

1.

6. The preparation method according to claim 1, characterized in that: The centrifugation condition is: 8000 rpm for 5 min.

7. The preparation method according to claim 1, characterized in that: The freeze-drying conditions in step (5) and step (10) are: vacuum drying at -60°C for 48 hours.

Citation Information

Patent Citations

  • Method for regulating and controlling interaction of starch and polyphenol by utilizing ultrahigh-pressure microjet

    CN113105649A

  • Printing method of 3D printing material based on cassava starch

    CN117297074A